KINERJA PELAYANAN PT. POS INDONESIA (PERSERO) KABUPATEN SRAGEN - Trilestari, Deny (Transformasi, 2015)
This study aims to analyze the performance of services by PT. Pos Indonesia (Persero)Sragen. Indicators that can be measured by reference to some concept of performance:Productivity, Quality layananan, Responsiveness, Responsibility and akuntabelitas that arefound to improve the performance of the service. The method used is descriptive qualitative.Sampling was done by purposive sampling technique. The data used are primary data andsecondary data. The technique of collecting data through interviews, observation anddocumentation. Service Performance PT research results. Pos Indonesia (Persero) Sragenrated poorly in service of the public service users, evidence: first productivity seen from thedecline in the average type of product in the year 2012 in this case because foreigncompetition is more competent. The second orientation to the Customer Service Quality formof physical facilities in PT. Pos Indonesia (Persero) Sragen damage and lack of facilitieswhile employees of PT. Pos Indonesia (Persero) Sragen in serving the people less friendly.Third responsiveness, not yet fully meet the wishes of the people. Responsibility andaccountability PT. Pos Indonesia (Persero) Sragen has served in accordance with theMinimum Service Standards.Key word: services; performance; post.